Low nutrient and high chlorophyll a coastal upwelling system – A case study in the southern Taiwan Strait. (5th December 2015) - Hu, Jun; Lan, Wenlu; Huang, Bangqin; Chiang, Kuo-Ping; Hong, Huasheng
Abstract: Using the field data during four summer cruises of 2005, 2006, 2008 and 2013, an interesting phenomenon of low nutrient and high Chl. a (LNHC) was observed in the coastal upwelling system off Dongshan in the southern Taiwan Strait. The results indicated that the upwelling region was dominated by cold (<25 °C) and saline (>33.9 psu) upwelled water, and the concentration of nitrate (<1 μM) and phosphate (<0.1 μM) was very low, while with high Chl. a content (mean 1.98–3.56 μg L −1, maximum 8.3 μg L −1 ) during the stronger summer upwelling cruise of 2005, 2006 and 2008. The upwelled water originated from the 50–100 m layer off Shanwei with a low concentration of nitrate (<7.5 μmol·L −1 ) and phosphate (<0.5 μmol·L −1 ), which was transported to Shantou-Dongshan by the northeastward bottom current. During the time that the upwelled water moved the long-distance (150–300 km) from Shanwei to Shantou-Dongshan and was transported through the euphotic zone alongshore, the phytoplankton grew rapidly due to the favorable temperature, N/P ratio and illumination, and consumed most of the nutrients in the upwelled water. These unique physical, chemical and biological processes are the main reasons for the formation of the low nutrients/high chlorophyll a in this coastal upwelling system in the southern Taiwan Strait.